Screening of the novel antimicrobial drug, XF-73, against 2,527 Staphylococcus species clinical isolates - Rhys-Williams, William; Galvin, Helen Marie; Love, William Guy (Frontiers in Cellular and Infection Microbiology, 2023)
XF-73 (exeporfinium chloride) is a synthetic, di-cationic porphyrin derivative with rapid, potent bactericidal properties and a low propensity for engendering bacterial resistance. It is being developed clinically for the decolonization of Staphylococcus aureus in the nasal cavity to prevent post-operative staphylococcal infections. This study reports the minimum inhibitory concentration (MIC) of XF-73 in comparison to 22 antibiotics against a panel of >2,500 clinical isolates composed of 16 different Coagulase-positive and -negative Staphylococcus species from 33 countries. XF-73 was found to be effective against all isolates tested, with MICs ranging between ≤0.12 – 4 µg/ml (MIC50 and MIC90 values of 0.5 and 1 µg/ml respectively). XF-73 was found to be equally effective against antibiotic resistant isolates as antibiotic sensitive isolates, with no impact of pre-existing antibiotic resistance mechanisms to cell wall synthesis inhibitors (β-lactams, carbapenems, glycopeptides and cephalosporins), protein synthesis inhibitors (oxazolidinones, macrolides and tetracyclines), DNA synthesis inhibitors (fluoroquinolones) and a folate synthesis inhibitor. The panel selected also included examples of multidrug-resistant S. aureus isolates and, in all cases, the XF-73 MIC ranges were found to be similar against each of these groups. This dataset expands the knowledge of the breadth of activity of this novel antibacterial against a wide range of global S. aureus isolates and supports the potential utility of XF-73 for the treatment of patients who are S. aureus nasal carriers. Similar results were also obtained for multidrug-resistant isolates of other Staphylococcus species included in the study and collectively support the continued clinical development of XF-73 as an effective anti-staphylococcal drug.